Beam forming using neural network - Chua, Kee Siong. (2010)
This report presents the development of a neural network for beam forming. This model uses Back propagation techniques for the training of the neural network. It was developed on a Pentium system. Since the approach of neural network in beam forming is a rather new area, much time and effort were spent on the development and testing of different models to verify the suitability of the neural network for beam forming. This report records all the models tested and the final model adopted.